Two Different Views on Grief and Agony as Mental Pains In Emily Dickinson's Poems - Naila Amilia Satria (English Department, Faculty of Humanities, Andalas University, 2019)
This research looks at two poems of Emily Dickinson which are “I Measure Every Grief I Meet” and “I like a look of Agony”. The goal of this research is to show different views on grief and agony as mental pains in order to gain a better understanding of the two poems. The writer applies New Criticism approach and uses comparative method in order to get evidences that are needed. The text focuses on pointing out different views on grief or mental pain through attitudes of the speakers in each poem by analyzing the two poems stanza-by-stanza. This paper affirms that even though the two poems have same theme which are grief and agony or mental pain, the attitude of each speaker towards these issues is significantly different. In